A Phenomenological Inquiry into Wahdah Islamiyah’s Attitude toward Philosophy: Negotiating Purification and Intellectual Tradition - Wulandari, Andi Ulfa (Jurnal Pemikiran Islam, 2025)
This study examines Wahdah Islamiyah’s perspective on philosophy within the wider Islamic intellectual tradition, focusing on how resistance to philosophical inquiry unfolds within the organization’s culture. Using a phenomenological approach—combining observation, interviews, and document analysis—the research uncovers how Wahdah Islamiyah navigates the tension between engagement with philosophy and the imperative of religious purification. While previous studies have discussed Wahdah Islamiyah’s roles in law, education, and politics, little attention has been given to its ideological stance on philosophy itself. The findings show that Wahdah Islamiyah does not wholly reject philosophy, but imposes strict boundaries on its study, motivated by the belief that potential harm outweighs possible benefit. Members adopt a selective attitude toward religious texts, and practices deemed as innovation—those lacking clear scriptural basis—are generally avoided. The study argues that Wahdah Islamiyah should be viewed not just through normative or political frameworks, but as an ideological movement negotiating its position within Indonesia’s evolving intellectual landscape. Further research is encouraged to examine other Islamic organizations and the ongoing development of Islamic philosophy in Indonesia.